24‐nt phasiRNAs move from tapetal to meiotic cells in maize anthers. Issue 2 (20th May 2022) - Zhou, Xue; Huang, Kun; Teng, Chong; Abdelgawad, Ahmed; Batish, Mona; Meyers, Blake C.; Walbot, Virginia
Summary: In maize, 24‐nt phased, secondary small interfering RNAs (phasiRNAs) are abundant in meiotic stage anthers, but their distribution and functions are not precisely known. Using laser capture microdissection, we analyzed tapetal cells, meiocytes and other somatic cells at several stages of anther development to establish the timing of 24‐ PHAS precursor transcripts and the 24‐nt phasiRNA products. By integrating RNA and small RNA profiling plus single‐molecule and small RNA FISH (smFISH or sRNA‐FISH) spatial detection, we demonstrate that the tapetum is the primary site of 24‐ PHAS precursor and Dcl5 transcripts and the resulting 24‐nt phasiRNAs. Interestingly, 24‐nt phasiRNAs accumulate in all cell types, with the highest levels in meiocytes, followed by tapetum. Our data support the conclusion that 24‐nt phasiRNAs are mobile from tapetum to meiocytes and to other somatic cells. We discuss possible roles for 24‐nt phasiRNAs in anther cell types.